Penyusunan dan Penetapan Rencana Pembangunan Jangka Menengah Desa dan Rencana Kerja Pemerintah Desa - Sukriono, Didik (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aimed to describe the implementation of the preparation and determination of the Village Medium Term Development Plan and the Village Government Work Plan and the factors that influenced their preparation and stipulation. This research used an empirical juridical legal approach or sociological legal research, with a sociological juridical research type. The types of data in this study include primary, secondary, and tertiary data obtained through observation, documentation, interviews, focus group discussions, and conventional and electronic literature studies. The data were analyzed using qualitative juridical methods. The implementation of the preparation and stipulation of Village Mid-Term Development Plans and Village Government Work Plans in most villages was still “legally flawed and sociologically flawed”, starting from the formation of a compilation team, data collection, assessing potential and problems, aligning policy directions for district development planning, drafting designs, discussions, and the stipulation had not been implemented as instructed by the statutory regulation on villages. Factors that influenced the formulation and determination were categorized into factors that cause formal and material defects and factors that cause juridical-sociological defects. The factors that were causing formal and material defects include juridical, political, human resources, and community culture factors. The factors that were causing juridical-sociological defects include political, juridical, lack of facilities, technology, and culture.